The effect of giving organic fertilizers with different types on the concentration of Chorella sp. visually - Gita Usman; Nurqadri Syaia Bakti; Laisi Laisi; Pelmas Hidayat Gugule (Fisheries and Society Publisher, 2023)
Chorella sp. is a natural food that can support the growth of fish larvae. This microalgae is also very easy to find in inland waters, and can grow quickly if you get a good supply of nutrients and lighting. Chorella sp. can be cultivated simply by using 5 watt LED lighting and nourishing it using organic fertilizer. Chorella sp. culture carried out for 6 days with observations of 0 days, 3 days and 6 days. The use of different commercial organic fertilizers has an effect on the concentration of Chorella sp. The use of Bio plus organic fertilizer increases the discoloration of the culture media much more quickly during the rearing period compared to using MA11 organic fertilizer.